2015
DOI: 10.3727/096368914x684592
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Costimulator Gene-Transduced Bone Marrow-Derived Mesenchymal Stem Cells Attenuate the Severity of Acute Graft-Versus-Host Disease in Mouse Models

Abstract: In murine allogeneic transplantation models, ICOS gene-transduced bone marrow-derived mesenchymal stem cells (MSCs ICOS-EGFP ) were evaluated for their effects on GvHD severity and long-term survival. Lethally irradiated BALB/c or first filial generation of BALB/c and C57BL/6 (CB6F1) mice were transplanted with bone marrow cells and splenocytes from C57BL/6 mice to establish acute GvHD models. Recipient mice were injected with MSCs ICOS-EGFP , MSCs, MSCs EGFP , ICOS-Ig fusion protein, MSCs + ICOS-Ig, or PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Thus, as gene delivery vehicles, the localization of ADSCs combined with costimulation blockade may provide a new opportunity for successful therapy (15,42). In this study, our results revealed that the administration of OX40Ig gene-modified ADSCs resulted in a modest, but greater prolongation in the survival time of renal grafts compared with ADSC monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as gene delivery vehicles, the localization of ADSCs combined with costimulation blockade may provide a new opportunity for successful therapy (15,42). In this study, our results revealed that the administration of OX40Ig gene-modified ADSCs resulted in a modest, but greater prolongation in the survival time of renal grafts compared with ADSC monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were monitored daily for any clinical features including alopecia, submandibular erythema, hunchback appearance, and piloerection. A clinical disease severity score was assessed, where each of the aforementioned features were given a score of 1, as described previously (44,45).…”
Section: Methodsmentioning
confidence: 99%
“…There was significant heterogeneity among the studies (I 2 = 66.1%, P = 2.12×10 −18 ) (Figure 1 ). In addition, 29 studies involving 41 comparisons examined the effect of MSCs on aGVHD-associated clinical scores [ 14 , 15 , 17 , 19 , 20 , 22 , 24 , 27 , 28 , 33 , 34 , 36 39 , 42 , 44 , 46 , 47 , 49 52 , 55 , 57 59 , 61 , 62 ]. The pooled analysis indicated that aGVHD-associated clinical scores were significantly lower in the MSC groups than in the control groups (SMD = −3.60, 95% CI −4.43 to −2.76, P = 3.61×10 −17 ) (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%